2018
DOI: 10.5194/hess-22-2575-2018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of remotely sensed soil moisture and precipitation on soil moisture prediction in a data assimilation system with the JULES land surface model

Abstract: We show that satellite-derived estimates of shallow soil moisture can be used to calibrate a land surface model at the regional scale in Ghana, using data assimilation techniques. The modified calibration significantly improves model estimation of soil moisture. Specifically, we find an 18 % reduction in unbiased root-mean-squared differences in the north of Ghana and a 21 % reduction in the south of Ghana for a 5-year hindcast after assimilating a single year of soil moisture observations to update model para… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 49 publications
0
51
0
Order By: Relevance
“…A recent study has shown that assimilating SMOS SM data into the Noah Land Information System after bias correction significantly increased the anomaly correlation of modeled top soil moisture estimates with station measurements [45]. Also, Pinnington et al [46] showed that assimilation of (bias-corrected) satellite rainfall and SM data had the greatest impact on model estimates during the seasonal wetting-up and drying-down of the soil, respectively. While L-band satellites have been designed for measuring soil moisture, land surface models have been designed for a much wider purpose, including ecological, hydrological or climate applications.…”
Section: Comparison Of Smos Gldas-noah Era5 and In-situ At Target Smentioning
confidence: 99%
“…A recent study has shown that assimilating SMOS SM data into the Noah Land Information System after bias correction significantly increased the anomaly correlation of modeled top soil moisture estimates with station measurements [45]. Also, Pinnington et al [46] showed that assimilation of (bias-corrected) satellite rainfall and SM data had the greatest impact on model estimates during the seasonal wetting-up and drying-down of the soil, respectively. While L-band satellites have been designed for measuring soil moisture, land surface models have been designed for a much wider purpose, including ecological, hydrological or climate applications.…”
Section: Comparison Of Smos Gldas-noah Era5 and In-situ At Target Smentioning
confidence: 99%
“…These LDASs either optimize process parameters (e.g., CCDAS), state variables (e.g., GLDAS, NCA-LDAS, LDAS-Monde) or both (e.g., CLVLDAS). Assimilated Earth Observations (EOs) generally include satellite retrieval of surface soil moisture [5,8,[23][24][25], snow depth [26][27][28][29] and snow cover [9,27,30,31], vegetation [7,18,[32][33][34][35], as well as terrestrial water storage [36][37][38]. Few studies have included multiple remote sensing measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Those systems either optimize process parameters (e.g., CCDAS), state variables (e.g., GLDAS, NCA-LDAS, LDAS-Monde), or both (e.g., CLVLDAS). Only few studies have considered the integration of multiple remote sensing measurements [17,19] and even less have had a specific focus over West Africa (e.g., [21]).…”
Section: Introductionmentioning
confidence: 99%